Adaptation of clinical practice guideline for colorectal cancer screening in people with average risk in Isfahan province - Elham Tabesh; Maryam Ghassami; Reza Rezayatmand; Marzieh Tahmasebi; Payman Adibi (International Journal of Preventive Medicine, 2022)
Background: Colorectal cancer (CRC) is the third most common cancer among adults in Iran. The aim of colorectal cancer screening is to reduce the cancer burden in the population by diagnosing the disease in its early stages. Methods: We adapted this guideline for the moderate CRC risk population for Isfahan to determine how to screen them and when to start and end the CRC screening. This guideline was developed by clinical appraisal and review of the evidence, available clinical guidelines, and in consultation with members of the Isfahan Chamber of Iranian association of gastroenterology and hepatology. Results: In screening people with average risk for CRC who use personal resources and personally pay all the costs, colonoscopy is recommended as the first choice to be done every 10 years. In case of negative colonoscopy, we recommend FIT test to prevention of interval cancer every 5 years. In screening of people with average risk of CRC, FIT is suggested to be done every 2 years as a first-choice method test for those who use public resources and do not pay for this service personally. In screening individuals with average risk for CRC, g-FOBT is not recommended as the first method of choice. Repeating positive guaiac test is not recommended and if positive, colonoscopy is suggested.